Collaborative Planning of Multi-type and Multi-region Integrated Energy System - DENG Xin; DAI Qiongdan (Kongzhi Yu Xinxi Jishu)
With the development of economy and the improvement of consumption level, people’s requirements for improving energy utilization efficiency have entered into a new level, and the research of comprehensive energy system is emerging. To solve the problem of multi-type and multi-region integrated energy system collaborative planning, according to the different load characteristics, a planning area was divided into different regions; then, a CCHP (combined cooling, heating and power) system based collaborative planning model was established, and the Yalmip toolbox and CPLEX were used to analyze the model to get the capacity planning of equipment in different regions. Simulation results show that the multi-type and multi-region integrated energy system collaborative planning can improve the economic efficiency of the comprehensive energy system.